Taking care of youth mentoring relationships: red flags, repair, and respectful resolution. Issue 3 (27th May 2017) - MacCallum, Judith; Beltman, Susan; Coffey, Anne; Cooper, Trudi
Abstract: Mentoring is portrayed in the literature as benefiting young people, but ineffective or early termination of youth mentoring relationships can be detrimental. Researchers have not adequately explored issues surrounding the breakdown of youth mentoring relationships. Underpinned by a socio-ecological perspective, in this exploratory study we consider the various contexts within which these important relationships exist and identify early warning signs or red flags that a mentoring relationship is struggling. We interviewed mentees, mentors, and coordinators from four Western Australian youth mentoring programs about their experiences of mentoring relationships. Our findings suggest that red flags and repair strategies may be specific to particular programs, and that program coordinators play an important role in supporting relationships. Our research will help youth mentoring programs work toward early intervention strategies or appropriate and respectful termination of a relationship.